CRITICAL DISCOURSE ANALYSIS (CDA): A PATHWAY TO SHED LIGHT ON IDEOLOGY - Nurul Choyimah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2010)
Critical discourse analysts believe that language is not a neutral medium given that it might serve as an ideological purpose. As believed by Fairclough, ideology could be won by meaning construction. Choice of words matters in this case. This is because one might create meaning through his choice of words. A precise choice of words might have a great impact. Even, it is believed that the meaning of discourse may function as a generator machine that could shape realities or even change the world. Some cases in point indicate that choice of words contributes a lot to the process of shaping realities. In addition to meaning, sentence structure contributes a lot in meaning construction. Studying the discourse practice and sociocultural practice are another components of discourse which could be made use of the medium to uncover the ideology of the discourse producer. Indonesian Idol, a title attributed to the winner of a singing contest broadcast on RCTI, is a concrete example which gives credence to the notion that our choice of words is able to shape realities or even change the world. The meaning created by a discourse producer through his choice of words might sound natural for the public if it is intensively repeated and massively spread. This article explores how Critical Discourse Analysis touches upon the linkage between language and social practice.